若(3x-1)7=a7x7+a6x6+…a1x+a0,求:(1)a1+a2+…+a7;(2)a1+a3+a5+a7;(3)a0+a2+a4+a6
若(3x-1)7=a7x7+a6x6+…a1x+a0,求:(1)a1+a2+…+a7;(2)a1+a3+a5+a7;(3)a0+a2+a4+a6....
若(3x-1)7=a7x7+a6x6+…a1x+a0,求:(1)a1+a2+…+a7;(2)a1+a3+a5+a7;(3)a0+a2+a4+a6.
展开
展开全部
(1)∵(3x-1)7=a7x7+a6x6+…a1x+a0,
∴令x=1,得:(3×1-1)7=a7+a6+…a1+a0=27,①
又a0=
?(-1)7=-1.
∴a1+a2+…+a7=27+1=129;
(2)在(3x-1)7=a7x7+a6x6+…a1x+a0中,
令x=-1,则-a7+a6-a5+a4-…+a0=(-4)7②
由①-②得:2(a1+a3+a5+a7)=27-(-4)7,
∴a1+a3+a5+a7=8256.
(3)由①+②得:2(a0+a2+a4+a6)=27+(-4)7,
∴a0+a2+a4+a6=-8128.
∴令x=1,得:(3×1-1)7=a7+a6+…a1+a0=27,①
又a0=
C | 7 7 |
∴a1+a2+…+a7=27+1=129;
(2)在(3x-1)7=a7x7+a6x6+…a1x+a0中,
令x=-1,则-a7+a6-a5+a4-…+a0=(-4)7②
由①-②得:2(a1+a3+a5+a7)=27-(-4)7,
∴a1+a3+a5+a7=8256.
(3)由①+②得:2(a0+a2+a4+a6)=27+(-4)7,
∴a0+a2+a4+a6=-8128.
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询